Capacitación tributaria para el sector exportador en el cantón La Maná, provincia de Cotopaxi - Mendoza Carvajal, Ruth Vilma (2016)
The investigation was developed with the purpose of determining the current situation on the knowledge in relating topics to taxes district attorneys administered by the Service of Internal Rents, that which was executed in the sector exporter of the Canton The Manna, what generates several difficulties associated with the tributary appropriate application of the normative one. For such a reason he/she settled down as general objective: To propose a Technical Memory for the tributary training of the referred sector. To give continuity to the outlined topic a methodology of non experimental investigation it was applied since the same one required that it is involved to the whole sector exporter of the Canton The Manna, of where all the necessary information was gathered applying technical of investigation like interviews and surveys.